KEPEMIMPINAN OTORITER DALAM MANAJEMEN PENDIDIKAN ISLAM - S, Suriagiri (Management of Education: Jurnal Manajemen Pendidikan Islam, 2021)
The type of leader becomes an important entity in the management of islamic education. Surely, then, ongoing leadership should have a particular type of leadership that is expected to be able to bring wealth to the institutions or organizations it leads. As the educational organizers have already known that good leadership will deliver institutions to good qualities as well. As for this research, it focuses on the existence of authoritarian leadership in islamic education management. The study aims to identify forms of authoritarian leadership and the effect of its application in islamic institutions, and in this study researchers use a qualitative descriptive approach by reviewing the related literature. The results of the study indicate that authoritarian leadership is not appropriate to be adopted within islamic institutions for long periods of time, given that the good effects they have are very small and are more dominated by adverse effects. Researchers have thus revealed that it is necessary to recondition to eliminate and exclude the presence of this type of authoritarian leadership within the islamic institutions of education.